Метод синтеза инвариантных к вариациям активного сопротивления ротора алгоритмов прямого векторного управления асинхронным двигателем - Пересада, Сергей Михайлович; Трандафилов, Владимир Николаевич (НТУ "ХПИ", 2013)
A design method of direct field-oriented control algorithms of induction motor invariant to rotor resistance variations is presented. The invariance is guaranteed by invariant full-order observer, which is designed in two steps: on the 1st – the scaled equivalent control obtained from equation of torque current estimation compensate a part of disturbance component in equation of estimation of rotor flux vector angular position; on the 2nd – auxiliary feedbacks are constructed to provide stability. Experimental testing confirmed theoretical conclusions and showed advantage of invariant algorithm over standard.
Design method of direct field-oriented control algorithms of induction motor invariant to rotor resistance variations
Keywords: полеориентированное управление; вектор потокосцепления ротора; прямое векторное управление; промасштабированное эквивалентное управление; корректирующие обратные связи; персистность возбуждения